Planar pentacoordinate carbons in CBe54− derivatives. Issue 6 (14th January 2015) - Grande-Aztatzi, Rafael; Cabellos, José Luis; Islas, Rafael; Infante, Ivan; Mercero, José M.; Restrepo, Albeiro; Merino, Gabriel
Abstract : Ab initio computations show that the global minimum structure of the CBe5 Li n n −4 clusters ( n = 1 to 5) contains a planar pentacoordinate carbon atom. Abstract : The potential energy surfaces of a series of clusters with formula CBe5 Li n n −4 ( n = 1 to 5) have been systematically explored. Our computations show that the lithium cations preserve the CBe5 4− pentagon, such that the global minimum structure for these series of clusters has a planar pentacoordinate carbon (ppC) atom. The systems are primarily connected via a network of multicenter σ-bonds, in which the C atom acts as σ-acceptor and this acceptance of charge is balanced by the donation of the 2p z electrons to the π-cloud. The induced magnetic field analysis suggests that the clusters with formula CBe5 Li n n −4 ( n = 1 to 5) are fully delocalized. The fact that these ppC-containing clusters are the lowest-energy forms on the corresponding potential energy surfaces raises expectations that these species can be prepared experimentally in the gas phase.